Evaluation of acute and subacute toxicity of oil liniment based on 4-((5-(decylthio)-4-methyl-4H-1,2,4-triazol-3-yl)methyl)morpholine - Shcherbyna, R. О.; Parchenko, V. V.; Martynyshyn, V.; Hunchak, V.; Щербина, Роман Олександрович; Парченко, Володимир Володимирович (My University, 2018)
Objective: It has now been demonstrated that compound 4-((5-(decylthio)-4-methyl-4H-1,2,4-triazol-3-yl)methyl)morpholine shows antifungal and antimicrobial activities. This study was aimed to estimate toxicity values of novel oil liniment, which is based on mentioned compound and has antifungal effect. Material and Method: Research was held in accordance with guidelines “Toxicological screening of new substances for animal safety products” and “Preclinical esearch of veterinary drugs”. Toxicity level (amount of toxic doses) and benchmark doses for subacute study were assessed in conditions of acute study. Experiments were conducted on male wistar rats using karber method. Result and Discussion: Findings in the research of the acute effect have shown that studied substance belongs to the group of low-toxic compounds in conditions of intragastric administration. All rats survived and completed subacute study, and daily administration of oil liniment in duration of 14 days did not cause possible changes in body and organ weight among animals in experimental groups. It was demonstrated that prolonged exposure to the liniment caused possible increase of ALP and LDH on the background of possible cholesterol decrease, which may be the evidence of cholestatic liver disease, and enhancement of permeability of the cell membranes, which may be highlighted by destructive changes in liver.
Keywords: 4-((5-(decylthio)-4-methyl-4H-1,2,4-triazol-3-yl)methyl)morpholine; rat; toxicity